A aquisição da escrita para uma fonoaudiologia tocada pela psicanálise - Andrade, Juliana Cristina Alves de (2012)
Introduction: letters are present in the universe of the subject even before his birth. When desired, the baby is previously spoken by a speech / writing, so that his symbolic presence precedes his physical presence in the world. It s possible to say that the child is both spoken and written by the "Other", "Other" which Lacan refers to as the treasury of signifiers in which the speaking subject is immersed. Objective: To propose a model of acquisition of writing before its formalization by the child, it another view: that writing emerges before the formal encounter between the child and the letters. Method: qualitative research that is supported on one side, by studies in the field of language acquisition represented mainly by Claudia De Lemos and on the other, by notions of trace, letter and writing as understood by psychoanalysis studies of Freud, Lacan and Allouch. Some of the data from this literature were reread in order to trace the entry of the child in the alphabetic speech. Results: the analyzed material indicated the presence of pre-literate traces, or rather a writing system that indicates the child's subjection to the Other, to their capture by language in both oral and written form. Conclusion: writing takes a special place in the functioning of language, and the contact with oral and writing speeches opens the entry of the child to "letters". The speech therapist must interpret the marks left by the child, not only as scribbles, but as indicative marks of a singular process of acquisition of the written form of language. Thus, withdraws the denial of knowledge and returns the writing-subject position to the child, that separates from the alienation to the trace of the other, to take the position of reader / writer